Binding energies in large ionic clusters from kinetic energy release measurements - Bruzzi, Eleonora (2014)
The determination of binding energy is a very important piece of information that an experiment can provide. We have devised a new experimental procedure to measure binding energies for unimolecular (metastable) decay of multiply charged metal ligand cluster ions in gas phase.